DISTRIBUTION OF NEW INDUSTRIAL ITEMS ON THE MARKET AND INDUSTRIAL TRANSPORT ASPECTS OF ENTERPRISES - Rodion Rogulin; Pavel Nechaev; Dmitry Pleshanov (Вестник Северо-Кавказского федерального университета)
This article proposes a comprehensive solution to the three linear programming problems: Production problem (classical formulation), Transport problem, Service problem. Similar tasks in the proposed complex formulation often arise at enterprises in the process of expanding production in the region or entering a new market for their products. The main algorithms for finding the optimal solution are considered, a complex problem is formulated, a model is built, and a solution algorithm is implemented. The proposed model can be used in any enterprise that opens production points and when determining the optimal output for the entire organization. The purpose of such organizations is to minimize production costs and the cost of transporting finished products, as well as maximizing profits.